Behavioral Changes in Education Triggered by AI Use: A Perspective Based on Human-Computer Interaction (HCI) Theory - Tari, I Dewa Ayu Eka Purba Dharma (The Indonesian Institute of Science and Technology Research, 2025)
The emergence of artificial intelligence (AI) in education has significantly altered how students and teachers interact with technology and one another. This article examines behavioral changes resulting from the use of AI in educational settings through the lens of Human-Computer Interaction (HCI) theory. Using a conceptual approach, this paper proposes a framework that explores cognitive, social, affective, ethical, and professional dimensions in human-AI educational interactions. The analysis shows that AI promotes personalized learning and increases efficiency, yet introduces new challenges such as cognitive dependence, role shifts among educators, and ethical risks. The implications of this article are intended for curriculum designers, educators, and educational technology developers seeking to foster ethical, critical, and collaborative learning ecosystems.